Analisis Kekalahan Petahana dalam Pemilihan Kepala Daerah Tahun 2024: Studi Kasus Kekalahan Agus Taolin sebagai Petahana dalam Pilkada 2024 di Kabupaten Belu - Emerensiana Mau; Yeftha Y. Sabaat; Stefanus Tri Admaja (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The phenomenon of incumbent defeat in the 2024 Belu Regency Election, particularly the defeat of Agus Taolin, who previously served as an active regional head, has become an interesting subject of study because incumbents generally have greater opportunities to win political contests due to their experience, political networks, and established popularity. This study aims to analyze the dynamics of incumbent defeat and the factors contributing to shifts in voter support. This research employs a qualitative approach using a descriptive-analytical method. Data were collected through in-depth interviews with community leaders, campaign teams, and voters, supported by observation and documentation. The analysis applies the Retrospective Voting theory to understand how the public evaluates incumbent performance based on their experiences during the administration period. The findings indicate that the incumbent’s defeat was influenced by negative public assessments of economic performance, public services, policies, and development programs, which were perceived as not fully meeting community expectations. Furthermore, limited communication and public involvement contributed to strengthening public dissatisfaction. Voter decisions reflected an evaluation of past performance, resulting in a “political punishment” through their choices at the ballot box.